Dessert mobile commerce application - Ang, Chyh Dian (2023)
This project is a mobile application designed specifically for small and medium-sized bakeries that want to manage their orders through an online platform. With the ability to upload images, earn points, check order history, and engage in dynamic transactions between sellers and buyers, this app provides an efficient and convenient solution for bakeries impacted by the COVID-19 pandemic. As many businesses struggle to operate outside of their physical locations, this app enables bakeries to continue serving their customers online, earning revenue and maintaining customer loyalty during these challenging times. This mobile commerce application serves as an ideal platform for small and medium-sized bakeries to sell their desserts. It eliminates the need for sellers to use social media platforms such as Instagram and Facebook for product uploads and advertisements. By providing features such as order management, image uploads, and customer engagement, the app offers a hassle-free solution for sellers to streamline their selling process. As a result, bakeries can expand their customer base, increase sales, and generate more revenue.